Genetic connectivity of the sky emperor, Lethrinus mahsena populations across a gradient of exploitation rates in coastal Kenya - Mzingirwa, F.A.; Stomeo, Francesca; Kaunda-Arara, B.; Nyunja, J.; Mujibi, F.D.N. (Frontiers Media, 2019)
Marine Protected Areas (MPAs) have the potential to enhance fisheries through transport of larvae or by a net emigration of adult and juvenile fish to adjacent fished areas. A network of appropriately located MPAs will have the potential to re-seed fished areas and other MPAs. Connectivity studies are therefore important to assess the effectiveness of a network of MPAs, and to determine the spatial scale necessary for spillover effects. The principal aim of this study was to determine the potential for Kenyan MPAs to re-seed adjacent fishing zones by evaluating the levels of genetic differentiation of populations of Lethrinus mahsena, a commercially important fish, along a continuum of protected and non-protected sites. Fish samples were collected from Marine Protected Areas (Mombasa and Kisite Mpunguti Marine Parks) and the fished reserves adjacent to the two MPAs. Total length and weight of the fish from the sites and fin clips from one of the pectoral fins were collected and preserved in 90% ethanol. Genomic profiles for each sample were obtained through Genotyping by Sequencing (GBS) using DArT markers. Results from population structure, diversity and admixture analyses indicated very low genetic differentiation (FST=0.00184, P>0.05) and low population sub-structure between samples obtained from the study locations implying a free exchange of fish across protected and non-protected sites. There was a high gene flow and multi-directional migration rate among the sampling sites. Inbreeding was moderately high (FIS=0.15, P<0.05) in the marine parks, indicating high relatedness and probably limited mating options for the species due to small population size or spatial restriction. The lack of genetic differentiation between protected areas and open fishing grounds is indicative of genetic connectivity for the sky emperor. This reinforces the significance of maintaining protected areas to serve as breeding and spawning grounds of fish without adversely affecting the livelihoods of communities that depend on the various fisheries linked to MPAs.